LOW SPEED GENERATOR DESIGN FOR SMALL SCALE HYDROKINETIC TURBINE APPLICATION - JORDAN ISAAC, ALISTAIR DING WAN (Universiti Malaysia Sarawak (UNIMAS), 2023)
This project aims to develop a low-speed permanent magnet generator intended for hydrokinetic applications, with a focus able to generate electrical output at a low speed of 300 revolutions per minute (RPM). The implementation of a large number of poles is used to optimize the performance of the generator. The expected impact of this research is that it could become one of the viable solutions to solve the problem of rural communities that experience limited access to electricity. Additionally, the outcomes of this research could contribute to the development of efficient and reliable low-speed generator technologies for hydrokinetic applications. The findings provide valuable insights into the design considerations and performance characteristics of such generators, which it could serve as a foundation for further advancements in the field of hydrokinetic turbine and encourage the exploration of low-speed generator technologies to harness renewable energy from hydrokinetic sources. Overall, this research aims to contribute to the development of more effective and sustainable energy solutions that can benefit rural communities by reducing the reliance on fossil fuels-based machines. The results of this project have the potential to be applied in a variety of settings, including residential and commercial, making it a valuable contribution to the field of renewable energy.